MURDER BY TREACHERY IN ISLAMIC AND INDONESIAN CRIMINAL LAW - Irfan, M. Nurul; Rosyid, Maskur; Faiz, Muhammad Fauzinudin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study examines the concept of qatl al-gh?lah (murder by treachery) in Islamic criminal law and its relevance to the reform of Indonesia’s national criminal law. The phenomenon of qatl al-gh?lah is an essential issue in the study of Islamic criminal law because it has characteristics that differ from other types of murder. From the perspective of Islamic jurisprudence (fiqh jin?yah), this crime is classified as murder whose punishment can only be enforced through qi??? and ??cannot be removed even if the victim’s family forgives. The relevance of this issue becomes increasingly evident when linked to several cases in Indonesia, such as the murder of Affan Kurniawan by a police officer, the Ferdy Sambo case, the KM 50 incident, and various other cases that demonstrate the weak protection of public security. However, previous studies rarely connect the normative concept of qatl al-gh?lah with practical issues in Indonesian positive criminal law, resulting in a gap in understanding how treachery-based murder should be legally qualified. Using a qualitative, normative approach through a literature review and case analysis, this study finds that qatl al-gh?lah warrants urgent attention in inspiring national criminal law reform. Its primary contribution is to provide a conceptual foundation for discussing the special category of murder based on exceptions, thereby integrating Islamic values of justice into the Indonesian criminal law system.